PAT-1 Case report: Metastatic ganglioneuroma in a Sumatran Tiger - E Handharyani; D R Agungpriyono; R W Wiranti; G K Suryaman; S Edwar; E Rumiyati; A Winarto (Hemera Zoa, 2018)
Neuroblastic tumors, which are uncommon tumors of nerve cell origin, are classified into neuroblastoma, ganglioneuroblastoma, and ganglioneuroma depend-ing on the degree of maturation of neoplastic neuroblasts and development of schwannian stroma [2,4,7]. Ganglioneuroma is a rare neuroectodermal tumor of the peripheral nervous system. Ganglio-neuromas generally are considered to be benign neoplasms composed of both mature ganglion cells and nerve fascicles with axons, Schwann cells, fibroblasts, and other connective tissue elements [1]. The aim of this study is to clarify the pathomor-phological feature of a subcutaneous ganglio-neuroma which occurred in a Sumatran tiger.